Implementation of Project-Based Learning Approach in Improving Critical Thinking Skills of Elementary School Students - Isnani, Tuti (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2023)
The implementation of project-based learning (PBL) approach has gained attention as an effective method to enhance critical thinking skills among elementary school students. This paper explores the effectiveness of implementing the PBL approach in improving critical thinking skills among elementary school students through a qualitative analysis based on literature review and library research. The study investigates various aspects of PBL implementation, including its principles, strategies, and outcomes related to critical thinking development. Findings suggest that PBL provides students with opportunities to engage in authentic, inquiry-based learning experiences that promote higher-order thinking skills such as analysis, evaluation, and synthesis. Moreover, the collaborative nature of PBL fosters communication, teamwork, and problem-solving abilities among students. By immersing students in real-world projects, PBL encourages active participation, creativity, and innovation, leading to a deeper understanding of concepts and issues. Additionally, the integration of technology and multimedia resources enhances the PBL experience, offering students diverse learning opportunities and increasing their motivation and engagement. The findings underscore the importance of well- designed PBL activities and supportive learning environments in maximizing the development of critical thinking skills. Overall, this research contributes to the existing literature by providing insights into the effectiveness of PBL in promoting critical thinking skills among elementary school students.